Psychometric properties of a revised Spanish 20-item Toronto Alexithymia Scale adaptation in multiple sclerosis patients - Eduardo Fernández-Jiménez (International Journal of Clinical and Health Psychology, 2013)
There have been a small number of investigations of alexithymia in multiple sclerosis (MS) using the 20-item Toronto Alexithymia Scale (TAS-20). However, the TAS-20 factor structure has not yet been evaluated in a MS patient sample, and earlier Spanish translations of this instrument require some improvement. We aimed to evaluate the factorial validity and reliability of an improved Spanish translation of the TAS-20 (the TAS-20-S). The TAS-20-S was completed by 221 MS patients. Confirmatory factor analysis was used to compare the fit of six different factor models. Internal consistency and retest reliability coefficients were also computed. The correlated three-factor model and the higher-order factor model made up of Difficulty Identifying Feelings, Difficulty Describing Feelings, and Externally Oriented Thinking achieved the best fit. Alpha coefficients ranged between .87 and .67; mean inter-item correlations ranged between .48 and .20; and retest correlations after 6 months ranged between .61 and .52. A high degree of alexithymia was present in 18.1% of the sample. Reliability and the traditional three-factor structure were demonstrated for the TAS-20-S, which can now be recommended for assessing an aspect of emotional processing in MS patients.